Sludge as a potential feedstock for thermochemical conversion a comprehensive characteristics study - Chen, Rong Fen (2015)
Municipal wastewater sludge handling and disposal has become a more and more challenging issue in both developed and developing countries. Sludge production is expected to grow while regulations on sludge disposal have been tightened due to concerns with its high toxicity. In the recent years, energy and material recovery of sludge via thermochemical conversions has attracted much attention in the scientific world. Performance of thermochemical conversions of sludge is largely dependent on the feedstock quality. Thus, comprehensive study of characteristics of sludge is a key component to thermochemical conversion of sludge. This report intended to investigate the characteristics of sludge in Singapore as a feedstock for thermochemical conversion. The characteristics study was done in three aspects, namely, inherent characteristics of sludge, biomass compositions of sludge and pyrolytic behaviors of sludge. Sludge samples of different types and batches from the same water reclamation plant were used in this report for comparisons of sludge characteristics across types and batched. Pelletized density, higher heating value (HHV), ultimate analysis and functional group analysis were performed to understand the properties of sludge mixture as received. Sequential extractions of sludge were conducted using ethanol and water as solvents in an attempt to gain a more insightful view of the possible biomass compositions in sludge. Thereafter, HHV, ultimate analysis and functional group analysis of the extraction residues and extractives were carried out. Sludge samples were placed for pyrolytic conversions under pre-set conditions followed by analysis on the product compositions. Pyrolytic product gases were further studied using gas chromatography where product chars were analyzed with calorific test, ultimate analysis and functional group identifications. In terms of inherent characteristics and biomass composition analysis, sludge samples of different types produced deviating properties in general whereas sludge samples of different batches showed close proximity. Nevertheless, consistent relative trends in the dry base HHV, CHNS compositions and functional group identifications among different types were observed. The analysis of the pyrolytic product compositions, on the other hand, indicated that both lower ash content and higher process temperature resulted in higher non-solid product composition and higher proportion of H2 and organic hydrocarbon gases liberated. Study of the functional groups present in chars obtained from different temperature depicted a trend in the relative ease of thermal conversion of certain functional groups.